Mentoring to empower researchers - Hopkins, Sam (Success in research., 2020)
Mentorship can be a rewarding experience for both the mentor and the mentee. Within this context, this book provides guidance on how to set up mentorship programmes in your institutions, and the skills of an effective mentor, including: • Mentorship for transition points, • Skills development needed for publication, funding application and networking, • Mentorship for performing supervision duties. This is a practical and easy-to-use guide that draws on the editors’ extensive experience, and an invaluable tool for practitioners, career advisors and academics working in research and skills development.